First time mothers’ experiences during Covid-19: a qualitative analysis - Gülcü, Ecem Merve Altan (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT: Transition to motherhood is difficult for most women, in addition to significant physical and psychological changes, they also need to learn a variety of parenting behaviors and adapt to new family bonds. Significant social, biological, and psychological changes occur throughout pregnancy and postpartum period. Even while most women anticipate pregnancy and motherhood with enthusiasm, doing so during a pandemic may be challenging and stressful (Draganovic et al., 2021). The effect of COVID-19 on psychological outcomes is anticipated to be significant when prenatal and postnatal changes are combined with the impact of the pandemic (Matvienko-Sikar et al., 2020). Factors such as the mother or newborn's fear of exposure to the virus, social isolation, reduced social support, inconsistency between birth and childcare expectations and actual experiences may all have contributed to a stressful postpartum period (Diamond et al., 2020). Moreover, postnatal women are at a higher risk of having depression, anxiety, and stress (Caparros-Gonzalez, 2020). The present study aims to understand Turkish first-time mothers’ experiences during the pandemic and how they interpreted the effects of the pandemic restrictions on their motherhood journeys. In-depth interviews were conducted with seven participants who had given birth to their first child at least 36 weeks into their pregnancy during the pandemic. Not having any significant newborn disease in the babies of the participants and normal development of the babies are among the participant criteria. Interpretative Phenomenological Analysis (IPA) of the interviews revealed four themes: getting ready for motherhood during the pandemic, need for connection, motherhood: a challenging journey and coping with the pandemic. The findings were discussed in the light of the existing literature, suggestions for future research were presented and the contribution of the subject to clinical applications was discussed.

ÖZET: Anneliğe geçiş çoğu kadın için zordur, önemli fiziksel ve psikolojik değişikliklerin yanı sıra çeşitli ebeveynlik davranışlarını öğrenmeleri ve yeni aile bağlarına uyum sağlamaları gerekir. Hamilelik ve doğum sonrası dönemde önemli sosyal, biyolojik ve psikolojik değişiklikler meydana gelir. Çoğu kadın hamileliği ve anneliği hevesle beklerken, bir pandemi sırasında bunu yapmak zor ve stresli olabilir (Draganovic vd., 2021). Doğum öncesi ve doğum sonrası değişiklikler pandeminin etkisi ile birleştirildiğinde COVID-19'un psikolojik sonuçlar üzerindeki etkisinin önemli olması beklenmektedir (Matvienko-Sikar vd., 2020). Anne veya yeni doğanın virüse maruz kalma korkusu, sosyal izolasyon, sosyal desteğin azalması, doğum ve çocuk bakımı beklentileri ile gerçek deneyimler arasındaki tutarsızlık gibi faktörlerin tümü, stresli bir doğum sonrası döneme katkıda bulunmuş olabilir (Diamond vd., 2020). Ayrıca, doğum sonrası kadınların depresyon, anksiyete ve stres yaşama riski daha yüksektir (Caparros-Gonzalez, 2020). Bu çalışma, Türkiye'de ilk kez anne olacak annelerin pandemi sürecindeki deneyimlerini ve pandemi kısıtlamalarının annelik yolculuklarına etkilerini nasıl yorumladıklarını anlamayı amaçlamaktadır. Pandemi sırasında ilk çocuğunu, hamileliğinin en az 36. haftası itibari ile doğurmuş olan yedi katılımcı ile derinlemesine görüşmeler yapıldı. Katılımcıların bebeklerinde herhangi bir önemli yeni doğan hastalığı olmaması ve bebeklerin normal gelişim göstermesi katılımcı kriterleri arasındadır. Görüşmelerin Yorumlayıcı Fenomenolojik Analizi (IPA) dört temayı ortaya çıkardı: pandemide anneliğe hazırlanmak, bağlantı ihtiyacı, annelik: zorlu bir yolculuk ve pandemi ile başa çıkmak. Bulgular mevcut literatür ışığında tartışılmış, gelecek araştırmalar için öneriler sunulmuş ve konunun klinik uygulamalara katkısı tartışılmıştır.
İlk kez çocuk sahibi olmuş annelerin Covıd-19 dönemi deneyimleri: kalitatif analiz
Keywords: COVID-19; Pandemi; Anneliğe Geçiş; Doğum Sonrası; Pandemide Annelik; Pandemic; Transition to Motherhood; Postnatal Period; Motherhood During the Pandemic